Rare earth elements in the anatomical, nutritional and photosynthetic characteristics of Pistia stratiotes - Duarte, Ana Carolina Oliveira; Oliveira, Cynthia de; Castro, Evaristo Mauro de; Ramos, Sílvio Junio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
Abstract: Rare earth elements (ETR) are used by the technological industry and comprise phosphate fertilizers and their exploration and use on a large scale may result in an increase in the contamination of ETRs in the environment. Pistia stratiotes L. is known to be an efficient macrophyte in pollutant accumulation. The objective of the present work was to evaluate the effect of ETR concentrations (isolates and mixture) on morphoanatomical and nutritional characteristics, gas exchange and photosynthetic pigments of Pistia stratiotes. Gas exchange (photosynthesis analyzer - IRGA), chlorophyll content (chlorophyll meter - SPAD), and the anatomy of roots and leaves, nutrient content, and dry mass were evaluated. There was a reduction in plant growth and the root systems in treatments with a mixture of ETR and lanthanum (La). There is an increase in transpiration to maintain the flow, compensating for the loss of conductivity and allowing nutrients to reach the aerial part. The hoods are extended in La treatments to protect the meristematic region. The absorption of some nutrients are reduced due to the reduction of the root system. The barriers were thickened in the treatments with cerium (Ce). These changes occurred preventing the ETR from being absorbed and transported, causing negative effects on the plant.
Keywords: Water lettuce; Anatomy; Chlorophyll; ETR; Dry mass